Explaining the increased health care expenditures associated with gastroesophageal reflux disease among elderly Medicare beneficiaries with chronic obstructive pulmonary disease: a cost-decomposition analysis - Ajmera, Mayank (Dove Medical Press, 2014)
OBJECTIVE: To estimate excess health care expenditures associated with gastroesophageal reflux disease (GERD) among elderly individuals with chronic obstructive pulmonary disease (COPD) and examine the contribution of predisposing characteristics, enabling resources, need variables, personal health care practices, and external environment factors to the excess expenditures, using the Blinder–Oaxaca linear decomposition technique. METHODS: This study utilized a cross-sectional, retrospective study design, using data from multiple years (2006–2009) of the Medicare Current Beneficiary Survey linked with fee-for-service Medicare claims. Presence of COPD and GERD was identified using diagnoses codes. Health care expenditures consisted of inpatient, outpatient, prescription drugs, dental, medical provider, and other services. For the analysis, t-tests were used to examine unadjusted subgroup differences in average health care expenditures by the presence of GERD. Ordinary least squares regressions on log-transformed health care expenditures were conducted to estimate the excess health care expenditures associated with GERD. The Blinder–Oaxaca linear decomposition technique was used to determine the contribution of predisposing characteristics, enabling resources, need variables, personal health care practices, and external environment factors, to excess health care expenditures associated with GERD. RESULTS: Among elderly Medicare beneficiaries with COPD, 29.3% had co-occurring GERD. Elderly Medicare beneficiaries with COPD/GERD had 1.5 times higher ($36,793 vs $24,722 [P<0.001]) expenditures than did those with COPD/no GERD. Ordinary least squares regression revealed that individuals with COPD/GERD had 36.3% (P<0.001) higher expenditures than did those with COPD/no GERD. Overall, 30.9% to 43.6% of the differences in average health care expenditures were explained by differences in predisposing characteristics, enabling resources, need variables, personal health care practices, and external environment factors between the two groups. Need factors explained up to 41% of the differences in average health care expenditures between the two groups. CONCLUSION: Among elderly Medicare beneficiaries with COPD, the presence of GERD was associated with higher expenditures. Need factors primarily contributed to the differences in average health care expenditures, suggesting that the comanagement of chronic conditions may reduce excess health care expenditures associated with GERD.